Are risk-seekers more optimistic? Non-parametric approach - Weinstock, Eyal; Sonsino, Doron (Journal of economic behavior & organization, 2014)
•Lottery risk-preference significantly correlates with forecast optimism.•The correlations sustain when macro-expectations and demographics are accounted.•Win-chance optimism does not mediate the correlations.•The link dissolves when numeric anchors are provided.•Lottery-choice can be used for diagnosing susceptibility to unrealistic optimism. Class and field surveys revealed that personal inclination to take structured lottery-risk significantly correlates with optimism in financial forecasting. Trait optimism reflects in return predictions for successful and problematic stocks, in likelihood assessments of specific events, and even when respondents recollect past realizations. Gain-domain risk preference shows the strongest predictive power for forecast positivity, even when macro expectations, win-chance optimism and personal attributes are controlled. The correlations are strongest when optimism scores are derived from multiple prediction tasks, but quickly dissolve when subjects receive usable anchors. The findings are discussed in light of optimism scope and recent research on ambiguity aversion.